An Imitation of the Italian by Alexander Pushkin and The Hangman by Nikolai Markevich - Proskurin, Oleg (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2023)
This article presents a hypothesis regarding the possible source of one enigmatic episode in Alexander Pushkin’s poem An Imitation of the Italian (Подражание италиянскому, 1836). In this episode, demons (besy) liﬅ the corpse of Judas on their horns and laughingly drag him oﬀ to Satan. It is absent both in the Italian original, the sonnet Sopra Giuda by Francesco Gianni (1750–1822) and in its French translation by Antoni Deschamps (1800–1869), which served as the direct source for Pushkin’s imitation. Such demons do not exist in either the French or the Italian tradition. The article suggests that the source of Pushkin’s innovation is to be found in the poem Udavlennik (The Hangman) by the poet, musician, and collector of Ukrainian folklore Nikolai Markevich (1804–1860), published in the journal “Moskovskii Telegraf” in 1829 and included in his book Ukrainian Melodies, published in 1831. In the poem a Cossack who has committed suicide is carried oﬀ to hell on the horns of demons. Markevich was acquainted with Pushkin, having met him in Moscow in 1829. Ukrainian folk beliefs, poetically processed by N. Markevich, turned out to be perfectly suitable for expressing the characteristics of the Italian medieval consciousness.